Optimisation modelling of cancer growth - Jones, T.; Caccetta, Louis; Rehbock, Volker (2017)
Several computational models have been developed in the litera- ture to describe the dynamics of the cell-cycle for the mammalian cell, in par- ticular for cancer cells, using both traditional and new techniques and yielding some positive results. In this paper, we discuss how to optimise model param- eters for these types of models and how this can serve to enhance numerical results. We pose the model parameter selection problem as an optimal param- eter selection problem on both a normal cell and cancer cell cycle of growth. Various possible objectives are discussed and we illustrate the process with some numerical results.